2018
DOI: 10.1016/j.tiv.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Toxicologic/transport properties of NCS-382, a γ-hydroxybutyrate (GHB) receptor ligand, in neuronal and epithelial cells: Therapeutic implications for SSADH deficiency, a GABA metabolic disorder

Abstract: We report the in vitro assessment of pharmacotoxicity for the high-affinity GHB receptor ligand, NCS-382, using neuronal stem cells derived from mice with a targeted deletion of the aldehyde dehydrogenase 5a1 gene (succinic semialdehyde dehydrogenase(SSADH)-deficient mice). These animals represent a phenocopy of the human disorder of GABA metabolism, SSADH deficiency, that metabolically features accumulation of both GABA and the GABA-analog γ-hydroxybutyric acid in conjunction with a nonspecific neurological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Among the key regulators downregulated by ZIKV was ALDH5A1, the gene encoding a mitochondrial NAD(+) -dependent succinic semialdehyde dehydrogenase (SSADH) enzyme. In humans, SSADH deficiency is a rare autosomal recessive metabolic disorder affecting γ-aminobutyric acid degradation and is characterized by developmental delay, cognitive impairment, expressive language deficit, and mild ataxia 48 . Epilepsy is present in about half of affected individuals 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the key regulators downregulated by ZIKV was ALDH5A1, the gene encoding a mitochondrial NAD(+) -dependent succinic semialdehyde dehydrogenase (SSADH) enzyme. In humans, SSADH deficiency is a rare autosomal recessive metabolic disorder affecting γ-aminobutyric acid degradation and is characterized by developmental delay, cognitive impairment, expressive language deficit, and mild ataxia 48 . Epilepsy is present in about half of affected individuals 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression studies using NCS-382 in HepG2 cells revealed only a minor number of genes (of 370 tested) showing dysregulation (Table 1). Additionally, high-dose NCS-382 demonstrated only minimal pharmacotoxicity in neural stem cells (NSCs, or neuronal progenitor cells) derived from aldh5a1 −/− mice (e.g., aldh5a1 −/− NSCs) (Vogel et al, 2017e). These cells were developed as an in vitro model of SSADHD, showing increased GHB content in culture medium, enhanced biomarkers of oxidative stress and increased mitochondrial number and highlighting the utility of NSCs as a useful preclinical screening tool for evaluating therapeutics for SSADHD (Vogel et al, 2017f).…”
Section: Ncs-382 a Potential Novel Therapeutic For Ssadhdmentioning
confidence: 99%
“…Our objective here was to investigate the potential of NCS-382 to block uptake of GHB. We demonstrated for the first time using Madin-Darby Canine Kidney (MDCK) cells that NCS-382 is actively transported and capable of inhibiting GHB transport (Vogel et al, 2017e). Following these in vitro assays with in vivo studies in aldh5a1 −/− mice, we found the ratio of brain/liver GHB to be unaffected by chronic NCS-382 administration (300mg/kg; 7 consecutive days), which appeared paradoxical.…”
Section: Ncs-382 a Potential Novel Therapeutic For Ssadhdmentioning
confidence: 99%
“…Further studies using murine SSADHD models to correlate transcranial magnetic stimulation data with immunohistochemical and electrophysiologic data will be useful to better elucidate this inconsistency. 5,31,32…”
Section: Discussionmentioning
confidence: 99%